Detection and dynamics of circulating tumor cells in patients with high-risk prostate cancer treated with radiotherapy and hormones: a prospective phase II study - Almudena Zapatero; Antonio Gómez-Caamaño; María Ángeles Cabeza Rodriguez; Laura Muinelo-Romay; Carmen Martin de Vidales; Alicia Abalo; Patricia Calvo Crespo; Luis Leon Mateos; Carlos Olivier; Lorena Vega Vega Piris (Radiation Oncology, 2020)
Abstract Background Circulating tumor cells (CTCs) are an established prognostic marker in castration-resistant prostate cancer but have received little attention in localized high-risk disease. We studied the detection rate of CTCs in patients with high-risk prostate cancer before and after androgen deprivation therapy and radiotherapy to assess its value as a prognostic and monitoring marker. Patients and methods We performed a prospective analysis of CTCs in the peripheral blood of 65 treatment-naïve patients with high-risk prostate cancer. EpCAM-positive CTCs were enumerated using the CELLSEARCH system at 4 timepoints. A cut off of 0 vs ≥ 1 CTC/7.5 ml blood was defined as a threshold for negative versus positive CTCs status. Results CTCs were detected in 5/65 patients (7.5%) at diagnosis, 8/62 (12.9%) following neoadjuvant androgen deprivation and 11/59 (18.6%) at the end of radiotherapy, with a median CTC count/7.5 ml of 1 (range, 1–136). Only 1 patient presented a positive CTC result 9 months after radiotherapy. Positive CTC status (at any timepoint) was not significantly associated with any clinical or pathologic factors. However, when we analyzed variations in CTC patterns following treatment, we observed a significant association between conversion of CTCs and stages T3 (P = 0.044) and N1 (P = 0.002). Detection of CTCs was not significantly associated with overall survival (P > 0.40). Conclusions Our study showed a low detection rate for CTCs in patients with locally advanced high-risk prostate cancer. The finding of a de novo positive CTC count after androgen deprivation therapy is probably due to a passive mechanism associated with the destruction of the tumor. Further studies with larger samples and based on more accurate detection of CTCs are needed to determine the potential prognostic and therapeutic value of this approach in non-metastatic prostate cancer. Trial registration ClinicalTrials.gov ID: NCT01800058 .